Seminaire Bourbaki, volume 1994/95, exposes 790-804 - Seminaire Bourbaki; Seminaire Bourbaki , 1994/95 (Paris Societe Mathematique de France, 1996)
As in the preceding volumes of this seminar, one finds here fifteen survey lectures on topics of current interest : two lectures on operator algebras, two on algebraic groups, one on affine Hecke algebras and one on the algebraic geometry of affine space ; one lecture on abelian varieties over number fields, one on invariants of 3-dimensional manifolds, one on Verlinde's formula and one on mirror symmetry ; one lecture on the index of differential operators, one on the -Neumann problem and one on the Cauchy problem for PDEs.This volume also contains two lectures on Wiles' proof of the fact that semi-stable curves over are modular, which implies Fermat's last theorem.
Keywords: Homological algebra; Moduli; Operators